Playing Digital Game Motivations of University Students - Turgut, Murat; Yasar, Onur Mutlu (Asian Journal of Education and Training, 2019)
Digital gaming involves all kinds of activities, both individually and as a team, in an online or offline environment through an electronic device. It is stated that the age of playing digital games has decreased to 5-6 years. The aim of this study is to investigate the motivation of students in different faculties of Kastamonu University to play digital games according to gender, age, faculty, class, income and frequency of playing. The research is a descriptive research conducted with quantitative research method. A total of 400 students participated from Kastamonu University in Turkey. In the research, digital game playing motivation scale developed by Munusturlar and Munusturlar (2018) was used as a measurement tool. In the study, the normal distribution of the data was determined by kurtosis and skewness values, and parametric analysis methods One-Way Anova and Independent T test were used. The motivation of the participants to play digital games was determined at medium and high levels. According to the results, differences were found according to the variables of gender, department, age, class and income status. According to a study of men playing digital games motivation levels are higher than women. In addition, participants with better financial status are more motivated to play digital games. In addition, older participants have higher motivation to play digital games.